Growing trees for the greater good – German agroforestry farmers are driven by self-transcendence values - Volckens, Valeska Maria; Husmann, Kai; Feil, Jan-Henning; Paul, Carola (Journal of rural studies, 2025)
Despite the German government's ambitious objective of expanding the area of agroforestry to 200,000 ha by 2027, German farmers have been slow to integrate this ecologically-friendly land-use practice into their farming portfolios. In view of this, previous studies have predominantly focused on the perceived barriers or attitudes of non-adopters to agroforestry uptake, while the pioneer's motivation to implement agroforestry has rarely been the subject of investigation. We aim to provide a deeper understanding of the underlying reasons of agroforestry farmers' behaviour, employing Shalom H. Schwartz's value theory. We hypothesise that German agroforestry farmers are more open to change and demonstrate a greater capacity for altruistic values compared to the average German farmer. Incorporating the ‘21-Item Portraits Value Questionnaire’ into an online survey facilitated an examination of the personal values of German agroforestry farmers and a comparison with previously surveyed values of German farmers. Our results provide a comprehensive description of the formerly undocumented population of German agroforestry farmers (N = 40), including characteristics of their farms and agroforestry systems. The overall value portrait reveals that the highly self-transcendent German agroforestry farmers exhibit a greater concern for the common good than any other group of farmers analysed to date. The low score for 'Self-Enhancement' suggests that the greater good is more important to agroforestry practitioners than their personal benefit. Our findings yield implications for the legal framework and promotional activities pertaining to agroforestry. •Characterisation of German agroforestry farms based on a novel dataset.•Comparison of Schwartz's values between agroforestry and conventional farmers.•German agroforestry adopters are driven by the common good and a pioneering spirit.•We recommend softening the CAP's agroforestry criteria and appropriate payments.